The Influence of Peer Education on the Level of Knowledge of HIV/Aids among High School Students in Padang City in 2019 - Susanti, Dewi; Yuniarti, Elsyie; ., Erwani; Marta Tasman, Auwilla (KnE Life Sciences, 2019)
There were 280.623 cases of people with HIV in 2017 in Indonesia. Padang as a city had the highest HIV rate in West Sumatera. Peer education is one method to improve the knowledge of adolescents about HIV/AIDS which can cause a positive change in among adolescents. The purpose of this study is to determine the effect of peer education on the level of knowledge of HIV/AIDS to high school students in Padang City in 2019. This type of research is Pre Experiment with One Group Pretest Posttest design. The research was conducted in high schools at Padang city between January 2019 and February 2019. The total population of high school students in Padang city amounts to 1000. Samples were taken by stratified random sampling with 60 samples. The instrument of collecting data in this research was done using a questionnaire on the knowledge of HIV/AIDS. The validity and reliability are verified. The result of the questionnaire was analyzed by the way of univariate and bivariate with paired t-test. The research result showed the average knowledge about HIV/AIDS before peer education about HIV/AIDS was given as 8,35 and after peer education as 13,95. The result of bivariate analysis shows that there is an influence of peer education on the level of knowledge of HIV/AIDS on high school students in Padang city (p-value = 0,000), so the researcher hopes high school in Padang city to increase the supporting infrastructure and also a consistent out of school schedule is needed for peer education program and facilitated coaching for peer educators.